THE RELATIONSHIP BETWEEN FAMILY’S SUPPORT WITH OBEDIENCE OF PREGNANT WOMEN IN CONSUMING IRON TABLETS (FE) (STUDIED IN THE VILLAGE OF WATUDAKON DISTRICT OF KESAMBEN JOMBANG REGENCY) - Sugik Aprilianto; Hidayatun Nufus; Dwi Prasetyaningati (Jurnal Keperawatan, 2013)
Iron requirement increase after pregnancy, iron supplementation is an effective way to prevent anemia due toiron deficiency. Anemia is due to non-compliance with the mother in consuming iron tablets. Family supportis very important to help remind women to consume iron tablets, one of the main factors the low compliancewomen due to forgot to consume iron tablets. Based on preliminary studied which was conducted frominterview result of 8 pregnant women obtained 5 pregnant women (62,5%) did not obey to consume irontablets, while 3 pregnant women (37,5%) kept in consuming iron tablets. This research aimed to analyze therelationship between family’s support with obedience of pregnant women in consuming iron tablets. Thisresearch design was analytic of cross sectional, the population was husband who had pregnant women inthird trimester as many as 36 respondents, taken samples a number of 33 people with purposive sampling.Independent variable of this research was family’s support and dependent variable was the obedience ofpregnant women in consuming iron tablets. The research instrument used was a questionnaire, testing databy statistic test of Spearman Rank’s with value of  = 0,05. Based on results showed majority (54,50%) ofhusband had support and mostly (57,60%) of pregnant women who did not obey in consuming iron tablets.The result of statistic test obtained value of  (0,001) < alpha (0,05), so H1 accepted. The conclusion of thisresearch is that there’s relationship between family’s support with obedience of pregnant women inconsuming iron tablets. It is expected for health workers to keep and increase enpowerment of family andcommunity by giving counseling about the important of iron during pregnancy.